Microglial exosomal miR-466i-5p induces brain injury via promoting hippocampal neuron apoptosis in heatstroke - Zhu, Jie; Chen, Yahong; Ji, Jingjing; Wang, Longyan; Xie, Guoqiang; Tang, Zhen; Qu, Xiangmeng; Liu, Zhifeng; Ren, Guangli (Frontiers in Immunology, 2022)
Abstract Background Brain injury is the main cause of poor prognosis in heatstroke (HS) patients due to heat stress induced neuronal apoptosis. However, as a new cross-talk way among cells, whether microglial exosomal-microRNAs (miRNAs) are involved in HS-induced neuron apoptosis has not been elucidated. Methods We established a heatstroke mouse model and a heat-stressed neuronal cellular model on HT22 cell line. Then we detected neuron apoptosis by histopathology and flow cytometry. The microglial exosomes are isolated by standard differential ultracentrifugation and characterized. Recipient neurons are treated with the control and HS exosomes, whereas in vivo, the exosomes were injected into mice tail vein. The internalization of HS microglial exosomes by neurons was tracked. And apoptosis of HT22 was evaluated by flow cytometry and western blot in vitro, TUNEL assay and immunohistochemistry in vivo. We screened miR-466i-5p as the mostly up-regulated microRNAs in HS exosomes by high-throughput sequencing and further conducted gene ontology (GO) pathway analysis. The effect and mechanism of HS exosomal miR-466i-5p on the induction of neuron apoptosis are demonstrated by nasal delivery of miR-466i-5p antagomir in vivo and transfecting miR-466i-5p mimics to HT22 in vitro. Results HS-induced an increase in neurons apoptosis. Microglial exosomes are identified and taken up by neurons which induced HT22 apoptosis in vivo and vitro. HS significantly changed the miRNA profiles of microglial exosomes based on high-throughput sequencing. We selected miR-466i-5p as a target. And upregulated miR-466i-5p induced neurons apoptosis in vivo and vitro experiments. The effects are exerted by targeting Bcl-2, activating caspase-3 to induce neurons apoptosis. Conclusions We demonstrate the effect of microglial exosomal miR-466i-5p on neurons apoptosis and reveals potentially Bcl-2/caspase-3 pathway in heatstroke. Key words: heatstroke, microglia, exosome, miR-466i-5p, neuron apoptosis